2007
DOI: 10.1016/j.envpol.2006.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Is the effect of silicon on rice uptake of arsenate (AsV) related to internal silicon concentrations, iron plaque and phosphate nutrition?

Abstract: Arsenate uptake by rice seedlings is affected by both Si (internal and external) and iron plaque on root surface. AbstractSolution culture experiments were conducted to investigate the effects of silicon (Si) on arsenate (As V ) uptake by rice. The addition of Si to the pretreatment or uptake solution significantly decreased shoot and root As concentrations (P < 0.001 and P < 0.05). The presence of Si in the pretreatment or uptake solution also significantly decreased shoot P concentrations (P < 0.001). The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 30 publications
5
35
3
Order By: Relevance
“…Our results indicated that adding Si reduced As concentrations in rice roots (p<0.005), straw (p<0.05), husks (p<0.001) and grain (Table 2). This was in agreement with previous studies, showing that Si addition significantly reduced As concentrations in rice roots and shoots grown in solution cultures ( (Guo et al, 2005(Guo et al, , 2007Tripathi et al, 2013). Fleck et al (2013) reported that Si application limited As(III) uptake and translocation into shoots and subsequent transportation into grain.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results indicated that adding Si reduced As concentrations in rice roots (p<0.005), straw (p<0.05), husks (p<0.001) and grain (Table 2). This was in agreement with previous studies, showing that Si addition significantly reduced As concentrations in rice roots and shoots grown in solution cultures ( (Guo et al, 2005(Guo et al, , 2007Tripathi et al, 2013). Fleck et al (2013) reported that Si application limited As(III) uptake and translocation into shoots and subsequent transportation into grain.…”
Section: Discussionsupporting
confidence: 83%
“…Transporter Lis1 acts as a major uptake channel for As(III) in rice plants and Lsi 2 plays an essential role in mediating As(III) translocation to shoots and subsequent accumulation in the grains (Ma et al, 2006(Ma et al, , 2008. Consequently competition for uptake and translocation between Si and As(III) occurs, and hydroponic experiments have demonstrated that addition of Si reduced As uptake and accumulation in rice (Guo et al, 2005(Guo et al, ,2007Tripathi et al, 2013). Fleck et al (2013) reported that Si application reduced As concentrations by 22% in brown and polished rice grains by suppressing As(III) transport.…”
Section: Introductionmentioning
confidence: 99%
“…Silicates are also well known to be effective in alleviating arsenic (As) stress in rice (Bogdan and Schenk 2008;2009;Guo et al 2005;Ma et al 2008). It has been shown that arsenite uptake by rice seedlings is affected by Si both external and internal plant (Guo et al 2007). However, the mechanisms involved in the alleviation effect of Si on uptake of As are so far not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy in the results demonstrates that root fertilization and foliage dressing of Se may result in different effects on the contents of various nutrients in rice grains. Foliage dressing or root fertilization with Si and Se fertilizers has been reported to reduce crop uptake of As and Cd (Neumann and Zur Nieden, 2001;Guo et al, 2007;Feng et al, 2013a,b,c), contributing to yield enhancement (Hu et al, 2002;Singh et al, 2005). However, foliage dressing with Se and Si did not significantly affect the grain yields of rice in the present study.…”
Section: Discussionmentioning
confidence: 99%